Tatalaksana Nyeri Postoperatif pada Infant - Widyastuti, Yunita; Sari, Djayanti; Hernandes, Crodia (Jurnal Komplikasi Anestesi, 2018)
Postoperative acute pain is an unavoidable problem in postoperative conditions. Effective relief of pain is of the most importance to treating patients undergoing surgery. Effective pain management has significant physiological benefits. Manyways for pain management, althought opioid is general pain management and Regional block is a popular techniques in paediatric pain management recently, wether for surgery or need of adequate analgesic condition.